The hormonal and morphological events of stimulated cycles in an in vitro fertilisation programme - van der Merwe, J V; Grace, A; Snyman, E (South African medical journal, 1987)
A better understanding of the physiological processes involved in the stimulated cycle for successful harvesting of mature eggs in an in vitro fertilisation programme is a prerequisite for obtaining good pregnancy results. The hormonal levels of oestradiol, luteinising hormone (LH) and follicle-stimulating hormone correlated with ultrasonographic studies of follicular growth, were followed during an in vitro fertilisation cycle giving an overall pregnancy rate of 32% per transfer procedure. The combined use of clomiphene citrate (Clomid; Mer-National) and human post-menopausal gonadotrophin (Pergonal; Script Intal) produces an average of 5.96 follicles per patient. Human chorionic gonadotrophin (HCG) was given prior to the oestrogen peak and no spontaneous LH peak occurred before the day of the HCG injection. Timing of this injection needs to be synchronised with definite hormonal and ultrasonography values.